Evaluating a partnership model of hospice enabled dementia care: A three-phased monitoring, focus group and interview study. (October 2022) - McLaughlin, Dorry; Hasson, Felicity; Reid, Joanne; Brazil, Kevin; Rutherford, Lesley; Stone, Carol; van der Steen, Jenny T; Ballentine, Joanne
Background: People with dementia and their caregivers often lack equitable access to hospice care which is a concern internationally. Domains of best practice in palliative care for this population exist and hospices are urged to become dementia friendly. Aim: This study aimed to evaluate the model of 'Hospice Enabled Dementia Partnership' mapped to international domains of best practice. Design: Three-phased monitoring, group interview and individual interview study using a formative evaluation framework. Setting/ Participants: The partnership model was a collaboration between a large specialist palliative care hospice, a dementia charity and a Health Care Trust in the United Kingdom. Service documents were subjected to documentary review of monitoring activity and key indicators of service success. Group interviews and individual interviews took place with family carers ( n = 12), health care professionals involved in delivering the service ( n = 32) and senior professionals ( n = 5) responsible for service commissioning in palliative or dementia care. Results: One hundred people with dementia were referred to the service between May 2016 and December 2017. Thirty-eight of the 42 people who died, achieved their preferred place of care and died at home. Four themes were derived from the data 'Impact of Dementia', 'Value of the Service', 'Information and Learning Needs' and 'Working in Partnership'. Conclusions: Positive outcomes resulted from this best practice model; achievement of preferred place of care and death at home, dual benefits of therapies for patients and families and partnership in cross working and learning between services. Replication of this model should be considered internationally.